Personal development as a condition of personality development - Gasiul, Henryk (Studia Psychologica: Theoria et praxis, 2002)
The article comprises analysis of the condition of personality development. It is hypothesized that understanding of personality development demands the determination of human nature. The psychological analyses indicate the special role of self motives such as striving to self meaning, freedom, responsibility, and so on. These motives then indicate human nature which could be determined as person nature (which leads directly to the necessity of accepting a personalistic view of human growth). The category of self motives also enables to implicate on person attributes. Taking into consideration the fundamental role of self motives it is supposed that their fulfillment becomes a condition of the way a personality develops. Revealing of individuality depends on the quality of realization of person attributes (which self motives indicate). Moreover, the way of person realization and consequently the way of personality development depend on the kind of interpersonal connections.